Penguatan Budaya Anti-Fraud pada Karyawan Perbankan sebagai Upaya Pencegahan Tindak Kecurangan - Endang Shyta Triana (Politeknik Piksi Ganesha Indonesia, 2026)
Fraud remains one of the main risks faced by Bank Perekonomian Rakyat (BPR), particularly due to limited internal control systems and limited human resource understanding. This community service activity focuses on strengthening an anti-fraud culture among BPR employees as a preventative measure to prevent fraud. The purpose of the service is to increase employee knowledge, awareness, and commitment to the implementation of integrity, ethics, and compliance values. The methods used include education, socialization of anti-fraud policies, interactive discussions, and case studies relevant to BPR operational practices. The results of the community service demonstrate an increase in employee understanding of the types and impacts of fraud, as well as the importance of individual roles in creating a transparent and accountable work environment. This activity has a positive impact on strengthening the BPR's organizational culture, which is oriented towards fraud prevention and public trust.